Risk Factors for Recurrent Upper Gastrointestinal Tract Bleeding after Esophageal Varices Ligation on Patients with Liver Cirrhosis - Syarif Hidayat; Dharmika Djojoningrat; Nurul Akbar; Nanang Sukmana; Sabarinah Prasetyo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2004)
Background: Upper gastrointestinal tract (GIT) bleeding on liver cirrhosis patients will increase morbidity and mortality. Recurrent bleeding’s risk rise after the first episode of variceal bleeding. The mortality risk also rises on each bleeding. Purpose: This study was done in order to identify the risk factors for the first episode of recurrent bleeding of upper GIT on liver cirrhosis patient. Evaluation of risk factors was based on preliminary data prior to ligation. Method: Evaluation of the upper GIT bleeding was done using anamnesis on the patients or their relatives by letter, home visits or telephone. The data on recurrent bleeding was obtained from medical records. They were evaluated on the 3rd month then 1st year after ligation. This study was a cross sectional study with retrospective data and a consecutive sampling method. Result: Bivariate analysis revealed the 3rd month’s risk factors for first episode of upper GIT bleeding were ascites, total bilirubin level of 2 mg/dL, hepatoma, Child-Pugh C classification of the liver function and red color sign on esophageal varices. The risk factors for the first episode of upper GIT bleeding on first year were age £ 60 years old, hepatoma, and red color sign (RCS) on esophageal varices. The differences between risk factors on upper GIT bleeding on the 3rd month and 1st year were likely due to intervention, collateral para-esophageal varices, medication that irritated GIT, physical activities, and differences on variceal obliteration rate related to variceal ligation. Conclusion: Risk factors for recurrent upper GIT bleeding that could be minimized were ascites, total bilirubin level, Child-Pugh classification and RCS. It was expected with parascentesis, diuretics, hepatoprotector medications and drugs that lowers portal hypertension (such as propranolol and isosorbid mononitrate), might improve those risk factors thus decreasing the risk for recurrent upper GIT bleeding. Keywords: Upper gastrointestinal tract, esophageal varices, liver cirrhotic